F-18 Fluoro-2-Deoxyglucose Positron Emission Tomography (PET)/Computed Tomography (CT) Imaging in Melanoma: Normal Variants, Pitfalls, and Artifacts - Momodu, Jaleelat I.; Vangu, Mboyo Di Tamba (Frontiers in Nuclear Medicine, 2022)
Multimodality imaging has revolutionized diagnostic imaging for several oncologic pathologies including melanoma. Although F-18 fluoro-2-deoxyglucose positron emission tomography/ computed tomography [18F]FDG PET/CT has a high sensitivity in stage III and IV melanoma, several normal variants, and imaging pitfalls may result in falsely increased or reduced tracer uptake that may negatively impact diagnostic accuracy. In addition to normal physiologic tracer uptake, differences in the biological and molecular characteristics of different types of melanoma are also responsible for pitfalls. For instance, [18F]FDG PET/CT has a low sensitivity for detecting brain metastases due to normal physiologic [18F]FDG uptake in brain tissue while hepatic metastases from cutaneous melanoma are more [18F]FDG-avid than hepatic metastases from uveal melanoma. With the introduction of immunotherapies for melanoma, treatment response assessment using [18F]FDG PET/CT has a reduced specificity. This is due to hypermetabolic immune-related adverse effects such as hepatitis, dermatitis, and colitis resulting in false-positive uptake. In addition, immune therapy-induced initial increase in tumor uptake followed by disease response (pseudo-progression) is a cause of false-positive scan interpretation. Specific technical artifacts impact disease detection in [18F]FDG PET/CT melanoma imaging. The identification of small metastatic lymph nodes and lung nodules may be limited by the resolution of the PET/CT camera (partial volume effect). Computed tomography (CT) attenuation correction results in less apparent skin and subcutaneous lesions. Pictorial illustrations will be central to this paper for the description of these normal variants, imaging artifacts, and pitfalls. It is critical for the imaging specialist to have a clear understanding of these potential limitations of 18F-FDG PET/CT imaging in individuals who are referred with melanoma.